Antagonistic Activities of Endophytic Fungi from Chili Pepper (Capsicum frutescens L.) Stems and Leaves against Colletotrichum sp. - Puspitarini, Sofia; Aji, Oktira Roka (Universitas Ahmad Dahlan, 2023)
Colletotrichum sp. is one of the type pathogenic fumgi that can cause antachnose diseases. One of the plants that can be attacked by antrachnose is cayenne pepper (Capsicum frutescens L.). This study attempts to determine the ability of endophytic fungi from the stems and leaves cayenne pepper (Capsicum frutescens L.). Methods: This study used dual culture method to determine the percentage of resistence to patogen Colletotrichum sp. and the area of growth endophytic fungi planted on PDA (Potato Dextrose Agar). Results:. There are 3 isolates from the stems and leaves of cayenne pepper that is JE-B4-C, JE-D5-C, dan JE-B1-C. Among all the isolates, the largest percentage of inhibition and growth area endophytic fungi were found in isolate JE-B4-C with each of 29,41% dan 58,04 cm2. Conclusions: Expected isolates JE-B4-C derived from the genus eupenicillium, while isolates JE-D5-C and JE-B1-C respectively derived from the genus Aspergillus and Neoscytalidium.